Metode Dakwah pada Anak Jalanan: Studi Kasus pada Forum Peduli Anak Jalanan (Forpanja) - Ahmad Adnan; Irma Syahril (STID DI AL-HIKMAH, 2015)
This study aims to determine effective methods of propaganda on street children, the method used and the factors supporting and preaching on street children. While this type of research is using qualitative research with an approach on the street children. Place and time for the street housed research Mampang Prapatan Kingdom 8. A RT / RW 06/03 South Jakarta. Data collection method in this research is to use the observation of researchers observed directly in the field and interview is a form of verbal communication that aims to obtain information from respondents. Instruments in this study using a questionnaire or a questionnaire that contains questions aimed to get a response or a response and information from the respondents and the worksheet is a sheet that was brought by investigators while conducting research. Data analysis and processing is a data analysis and processing is the process of organizing and sort the data into patterns, categories and basic description of the unit so that it can be found a theme and can formulate a working hypothesis as suggested by the data. After the data collected then the next is scarce data processing, data obtained and managed or analyzed by descriptive analysis is an analysis in narrative form and backed up by figures in the form of percentage.